Subjects of the announcer's enunciation in "The man who had not done anything" - Medina-Huamán, Josué-Yared (2021)
In this investigation the poem "The man who had done nothing" from La torre de las paradojas (1926) is studied through the speaker and his relationship with the subjects of his enunciation. As a result, the speaker of the poem represents the whole of the actants through the textual focus on their parts or objects. Thus, it is concluded that the actants remain incommunicado due to their conflicting perspectives to assess the same object.